Evaluation of a strategy-oriented method to identify and prioritise knowledge management initiatives in SMEs - Juan Ignacio Igartua; Jabier Retegi-Albisua; Maria Ruiz; Maitane Mindegia (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: This article presents the process followed for the definition, application and evaluation of a Strategy oriented method of identifying and prioritising Knowledge Management (KM) initiatives in small to medium enterprises. Design/methodology/approach: To develop the method, the research team conducted a review of literature about existing business strategies and processes and models of maturity in KM. Based on that, a first version of a method was proposed. Subsequently, a contrast was made through a focus group composed of regional development centres, new company promotion agencies and industry representatives. Then, a four-step method, named KM-EZAGUTUZ, for the identification and prioritisation of KM initiatives in SMEs was proposed. Then, a field test was performed in five companies. Findings: The conclusions obtained through the research show the validity of the method for SMEs to identify and prioritise KM initiatives. Research limitations/implications: More field test should be done to confirm the validity of the method and improve it. Practical implications: The method, developed and supported in a prototype tool, helps companies to determine and prioritise actions for a better KM in accordance with company strategies, in a short period of time. In addition, the method supports a common understanding of the strategic vision of the organisation among the participants in the process. Social implications: Management practices are usually designed for medium and large companies. The significant resources required make it difficult for SMEs to benefit from their implementation. Given that SMEs account for a large share of employment in countries and that they need to manage knowledge effectively, this research helps to address this important socio-economic need. Originality/value: The method described in the article combines Strategy, Knowledge Management and a user friendly identification and prioritization tool adapted to SMEs.
Keywords: 650; knowledge management; strategic management; management tools; SMEs